New data on the cockroaches previously attributed to the genus Duchailluia Rehn, 1933 (Dictyoptera: Blattidae: Blattinae) - Anisyutkin, Leonid N.; Telnov, Dmitry (Zootaxa, 2018)
The new species of the genus Duchailluia Rehn, 1933, D. ivindo sp. nov., is described from Gabon. The genus Distylopyga Bey-Bienko, 1965 is restored from synonymy with Duchailluia. Distylopyga beccalonii sp. nov. from Thailand is described. Neostylopyga yemenica (Bey-Bienko, 1969) comb. nov. is transferred from Duchailluia. A detailed morphological descriptions of the new species are given, N. yemenica is redescribed inclusive male genitalia. The male genitalia of N. yemenica is described for the first time. The subfamily Duchailluiinae Roth, 2003 synonymized with Blattinae Latreille, 1810.